Effectiveness Of Prehospital Trauma Triage Systems In Reducing Mortality And Delays In Care (The Review of Diabetic Studies, 2025)
Background: Trauma is a leading global cause of death and disability, and timely prehospital care plays a decisive role in survival. Prehospital trauma triage systems are designed to rapidly identify injury severity and guide EMS providers in transporting patients to the most appropriate trauma center. Over the past decade, advancements in triage algorithms and digital decision-support tools have accelerated efforts to reduce mortality and minimize delays in care.Objective: This systematic review evaluates the effectiveness of prehospital trauma triage systems in reducing mortality, improving time-to-care intervals, and enhancing triage accuracy across diverse EMS settings.Methods: Following PRISMA 2020 guidelines, a comprehensive search of PubMed, Scopus, Web of Science, and CINAHL was conducted for studies published between 2015 and 2025. Eligible studies included observational designs, cohort studies, quasi-experimental trials, simulation-based evaluations, and system-level analyses examining prehospital trauma triage and its effects on mortality, time intervals, and accuracy. Risk of bias was assessed using Joanna Briggs Institute (JBI) appraisal tools. A narrative synthesis approach was used due to heterogeneity across study designs and outcomes.Results: A total of 27 studies met inclusion criteria. Structured triage systems, including stepwise algorithms, FTDS-based models, and digital decision-support tools, were associated with reductions in trauma-related mortality (8%–18%) and improvements in key time intervals such as scene time, transport time, and time to definitive care. Triage accuracy ranged from 62% to 89%, with AI-supported models achieving accuracy above 90%. Undertriage remained a persistent concern, particularly in rural and resource-limited regions, while overtriage continued at moderate-to-high levels in urban systems. EMS provider training, geographic setting, and system integration were key determinants of triage effectiveness.Conclusion: Prehospital trauma triage systems are effective in improving survival and reducing delays in care when implemented within coordinated trauma networks and supported by well-trained EMS providers. While modern tools—including AI and digital aids—show promising improvements in accuracy and efficiency, persistent challenges such as undertriage in rural settings and overtriage in high-volume centers highlight the need for ongoing refinement. Future research should prioritize real-world validation of emerging technologies and context-specific strategies to strengthen global trauma systems.